Data analysis of suspended sediment for rivers / Mohd Radhwan Abdul Karim and Junaidah Ariffin - Abdul Karim, Mohd Radhwan; Ariffin, Junaidah (2001)
Data analysis of suspended sediment was made based from data taken from three rivers namely Sungai Lui, Sungai Semenyih and Sungai Langat in Selangor. The data were measured from four gauging stations namely Kajang and Dengkil along Sungai Langat, Kg. Lui along Sungai Lui and Kg Rinching along Sungai Semenyih. Observed river stages during the study were between 3.87 m and 77.36 m. Data covers flow discharges ranging from 2.053 m3/s to 87.792 m3/s. Observed velocities were between 0.411 m/s and 1.422 m/s with range of flow depths between 0.302 m to 3.227 m. Measured suspended load for the rivers were between 0.046 kg/s to as high as 118.305 kg/s. From this study it revealed that suspended load constitutes a large fraction of the total load. Thus it can be concluded that total load is dominated by suspended load in most rivers. The concentration of suspended sediment in relation to flow depth is established.